Enemy of the state - Smith, Will, 1968-; Hackman, Gene; Bruckenheimer, Jerry; Scott, Tony; Touchstone Home Video (firm); Scott Free Productions; on Simpson/Jerry Bruckheimer production (Burbank, CA : Touchstone Home Video : Buena Vista Home Entertainment [distributor], 1998)
A federal agency attempting to get Congressional approval of legislation allowing them to spy on citizens at will chase an attorney who has unwittingly come in possession of proof that that same agency killed a senator who opposed the legislation
Title from title screen
Subtitles in English, Thai, Mandarin, Malay and Korean
Director of photography, Dan Mindel ; production design, Benjamin Fernandez ; film editor, Chris Lebenzon ; music, Trevor Rabin, Harry Gregson-Williams ; witter, David Marconi
Cast : Will Smith, Gene Hackman, Jon Voight, Regina King, Loren King, Jake Busey
DVD format
Keywords: Conspiracies -- United States -- Drama; Detective and mystery films; Feature films